Identification of Bone Marrow-Derived Soluble Factors Regulating Human Mesenchymal Stem Cells for Bone Regeneration - Tsai, Tsung-Lin (Stem Cell Reports, 2017)
Maintaining properties of human bone marrow-derived mesenchymal stem cells (BMSCs) in culture for regenerative applications remains a great challenge. An emerging approach of constructing a culture environment mimicking the bone marrow niche to regulate BMSC activities has been developed. In this study, we have demonstrated a systematic approach to identify soluble factors of interest extracted from human bone marrow and used them in BMSC culture for tissue regeneration. We have found that lipocalin-2 and prolactin are key factors in bone marrow, involved in regulating BMSC activities. Treating the cell with lipocalin-2 and prolactin delays cellular senescence of BMSCs and primes the cell for osteogenesis and chondrogenesis. We have also demonstrated that BMSCs pretreated with lipocalin-2 and prolactin can enhance the repair of calvarial defects in mice. Together, our study provides research evidence of using a viable approach to prime BMSC properties in vitro for improving cell-based tissue regeneration in vivo.